Penerapan Teknik Level Angle Untuk Memperkuat Dramatik Dalam Penciptaan Film Fiksi “Genius Dari Syurga” - Febry Ayu Retno; Dani Manesah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The final work of art creation entitled the application of the level angle technique to strengthen the drama in the cinematography of the fiction film